2020
DOI: 10.3390/coatings10070698
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of High Dielectric Constant Zirconia-Based Materials for Gate Dielectric Application

Abstract: The high dielectric constant ZrO2, as one of the most promising gate dielectric materials for next generation semiconductor device, is expected to be introduced as a new high k dielectric layer to replace the traditional SiO2 gate dielectric. The electrical properties of ZrO2 films prepared by various deposition methods and the main methods to improve their electrical properties are introduced, including doping of nonmetal elements, metal doping design of pseudo-binary alloy system, new stacking structure, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 92 publications
0
18
0
2
Order By: Relevance
“…Nonetheless, it has been concluded earlier that the average k of disordered ZrO 2 as high as 22.2 can be considered [53]. Such permittivity values for crystalline and disordered ZrO 2 have been supported by a number of experimental studies and may be regarded as reference values for ZrO 2 films synthesized by various methods [54].…”
Section: Dielectric Propertiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, it has been concluded earlier that the average k of disordered ZrO 2 as high as 22.2 can be considered [53]. Such permittivity values for crystalline and disordered ZrO 2 have been supported by a number of experimental studies and may be regarded as reference values for ZrO 2 films synthesized by various methods [54].…”
Section: Dielectric Propertiesmentioning
confidence: 82%
“…In regard with the literature reporting the capacitive parameters of ZrO 2 -based thin films, a reader could attend a recent review paper by Xie et al [54] and references therein. The results reported to date allow one to conclude that the permittivity of capacitive ZrO 2based cells can vary between 7 and 37, depending on the processing parameters, thickness, structural order, and dopant metal in ZrO 2 , together with the electrode materials selected to complete the cell structure.…”
Section: Resistive Switching Performancementioning
confidence: 99%
“…Relaxor type of high dielectric materials were also reported for doped cubic zirconia phases. [41][42][43][44] We have envisaged that high polarizability of Bi 3+ ion couple with high k dielectric relaxation (high dielectric leakage) can generate superior oxide-ion conduction near T m (the temperature of the maximum dielectric permittivity). To realize the concept, we attempted the suitable dopping of Bi 3+ and Gd 3+ ions into ZrO 2 lattice to stabilize cubic phase of zirconia and found that the synergistic interaction by introducing a secondary substituent (Gd 3+ ions) enhances the oxide-ion vacancy transport within the percolation limit of ion transport inside the host structure at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The typical high-k materials with a large band gap are ZrO 2 and HfO 2 . 6,7 Several studies have shown that preferably the band gap for a high-k material should be above ~ 5 eV.…”
Section: Introductionmentioning
confidence: 99%